Prevalence and risk factors of keratoconus (including oxidative stress biomarkers) in a cohort study of Shiraz university of medical science employees in Iran - Sahar Mohaghegh; Haleh Kangari; Seyed Jalil Masoumi; Shahram Bamdad; Saeed Rahmani; Saeed Abdi; Nagham Fazil; Saeedeh Shahbazi (BMC Ophthalmology, 2023)
Abstract Background To determine the prevalence of keratoconus in Shiraz University of Medical Sciences Employees and the related risk factors including oxidative stress biomarkers. Methods 2546 subjects’ mean age ± SD, 40.35 ± 6.70 (46% male) were recruited. All participants underwent objective refraction using auto-refractometer and retinoscopy, followed by subjective refraction, and bio-microscopy. Pentacam imaging was performed for the detected keratoconus patients. The prevalence of keratoconus and frequency of the visual impairment among keratoconus cases were evaluated. Potential risk factors of sex, age, family history of keratoconus, body mass index ≥ 30 kg/m2, serum levels of glucose ≥ 100 mg/d, low-density-lipoprotein-cholesterol (LDL) ≥ 110 mg/dL, high-density-lipoprotein-cholesterol ≤ 40 mg/d, and triglycerides ≥ 150 mg/dL in the blood were evaluated. Results The prevalence of keratoconus at least in one eye was 0.98% (95% CI: 0.6- 1.4%). The best corrected visual acuity in the keratoconus group was 0.06 ± 0.1 and the rest of the population was 0.01 ± 0.07 logMAR (p < 0.001). The frequency of visual impairment in the keratoconus group was zero. Odds ratios of the family history of keratoconus (21.00, 95% CI: 9.00–48.00, p < 0.001) and LDL ≥ 110 mg/dL (3.00, 95% CI: 1.20–6.40, p = 0.01) were significant. Conclusions Keratoconus is rare and is not considered a risk factor for visual impairment. A family history of keratoconus and elevated serum LDL levels are contributing risk factors, suggesting an inflammatory background for the disease. Serum levels of LDL ≥ 110 mg/dL in the blood increased the risk of keratoconus three folds.